Mild steel drums ( heavy duty-fixed ends ) (BSI, 1950)
Drums (containers), Bulk storage containers, Containers, Low-carbon steels, Heavy-duty, Stoppers, Dimensions, Flammable materials, Welded joints, Sheet materials, Volume, Reinforcement, Pressure testing